دراسة أحصائية حول تقدير المساحة المزروعة لمحصول الشلب في محافظة النجف - علوان, اقبال محمود (Journal of Economics and Administrative Sciences, 2009)
The objective of the research is to find the best method to estimate rice crop through out evaluating the applied methods of stratified random sampling .By using different sorts of sampling estimators, a comparison was held among the variances of the mean for simple random sampling, stratified random sampling(var()) and separate regression estimator. The results indicate that the separate regression estimator give best estimations. The approximate cum.f4/5 method was used to determine the optimum stratum boundaries, new strata was put and then var () was calculated .In comparison with strata used nowadays in central statistical organization, the new strata led to obvious decrease in the variance. The stratified mean was estimated using the separate regression method for rice crop and comparing it with the population real estimate by testing   χ2 between the real and estimate value .